Alginate-like exopolysaccharide extracted from aerobic granular sludge as biosorbent for methylene blue: Thermodynamic, kinetic and isotherm studies. Issue 3 (June 2019) - Ladnorg, Sebastian; Junior, Nelson Libardi; Dall´ Agnol, Patricia; Domingos, Dayane Gonzaga; Magnus, Bruna Scandolara; Wichern, Marc; Gehring, Tito; da Costa, Rejane Helena Ribeiro
Graphical abstract: Abstract: The aim of this study was to investigate the applicability of alginate-like extracellular polymers extracted from aerobic granular sludge, as a novel and innovative biosorbent for the removal of the dye methylene blue from aqueous solutions. The adsorption process using alginate-like exopolysaccharide (ALE) was investigated examining the influence of pH, adsorbent dosage, temperature and initial dye concentration. Moreover, kinetic models and isotherms were applied to describe the adsorption process. Maximum dye removals of 69% were achieved under the temperature of 35 °C, which was obtained with a contact time of 60 min. The optimum pH and biosorbent dosage were 8.0 and 117 g/L, respectively. The best-fitted model for ALE adsorption was the Langmuir model, while the pseudo-first-order model describes the kinetic behavior of the adsorption process best. ALE displayed a very similar adsorption behavior compared to alginate beads, indicating the potential of this new and sustainable biosorbent, which can be directly produced from wastewater.